(untitled) (Eurasian Medical Research Periodical, 2024)
Forming medical information and statistics, performing the functions of a methodological and regulatory center for the development of uniform state and departmental reporting forms for all health care organizations in the health care system together with the State Statistics Committee of the Republic of Uzbekistan; The Ministry of Health and, if necessary, the Cabinet of Ministers of the Republic of Uzbekistan should be given the right to submit proposals on improving the health care system, the regulatory legal framework in the field of strengthening and maintaining the health of the population.